OVERVIEW THE IMPLEMENTATION OF FOOD SERVING SYSTEM ON THE SHIP OF KELUD – PT. PELNI, INDONESIA - Lela Mustikawati (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Food serving system on Kelud ship-PT. Pelni was done in large number of quantity because it was served for about 2000 passengers The purposes of research are to determine input, process, output and feedback from the implementation of food serving of Kelud ship. The research used qualitative method by using in-depth interviews and observations. The respondents is 24 people, they are first chip purser, chip of chef, crew of ship, gunroom and passengers of ship. The variables are input, process and output. Input consists of workers, fund, infrastructure and equipment; process consists of menu planning, raw material planning, purchasing, receiving, storage, processing, distribution, serving and hygiene sanitation; output consists of the taste of meal; feedback consists of reporting and evaluating. The results of research showed   the input of serving system on Kelud ship consists of 27 people, lack of infrastructure facilities; otherwise there is good and adequate equipment. The process of serving  food on Kelud ship used  weekly menu,  used recipes and food portion of standard operating procedures, purchasing by direct appointment, acceptance by using invoice receiving, storage separate  between dry and wet materials, food processing by using of numerous techniques, decentralized distribution, serving by using table service, buffet, and plato but lack of hygiene sanitation. The output consists of the appearance of the meal, for traveler 1st, 2nd and 3rdclass are already good, but for economy class, the taste of food is still not good. Feedback was done by personal discussion and inventory, while the evaluation was done through suggestion boxes and monthly meeting. The result of the research recommended PT. Pelni to do better hygiene and sanitation during process and distribution of food therefore there are no contaminations, better in serving and taste good of food so passengers are satisfy. Improvement in appearance and taste of the food is needed. Keywords: food serving, food system, food service, food management, food safety